Cultural Distance, Acculturative Stress, Functional Social Support, and Psychological Adaptation of International Students - Ariel Ladum; Gary Burkholder (Laureate Education Inc, 2019)
This study examined how cultural distance, acculturative stress, and social support interacted to influence emotional responses among international students studying in the northern part of Cyprus. Acculturation models and the stress-buffering hypothesis served as theoretical frameworks. The research questions involved understanding whether international students experienced more negative emotional responses compared to students from the home culture and whether social support moderated acculturative stress and reactions to being in the northern part of Cyprus. An analysis of variance (ANOVA) examined differences in emotional reactions between home and international students while hierarchical multiple regression was used to examine the moderation hypotheses. ANOVA results indicated that Turkish-Cypriots had more positive emotional responses than international students to being in the host culture. Results did not support social support as a moderator for either international students' acculturative stress or their emotional reactions. However, results suggested that unmet expectations, less financial satisfaction, and less social support predicted acculturative stress, while being in a relationship, higher Turkish proficiency, unmet expectations, and higher acculturative stress predicted more negative emotional responses. These results may help universities design programs to support psychological adaptation among international students, which could ultimately facilitate student retention.